Differences in Glenohumeral Range of Motion and Humeral Torsion Between Right-Handed and Left-Handed Professional Baseball Pitchers. Issue 9 (July 2022) - Harris, Jeremy; Maier, Jacob; Freeston, Jonathan; Soloff, Lonnie; Himmerick, Daniel; Pipkin, Andrew; Genin, Jason A.; Schickendantz, Mark S.; Frangiamore, Salvatore J.
Background: Elite pitchers have demonstrated significant differences in glenohumeral range of motion and humeral torsion compared with the nonthrowing population. Furthermore, abnormal shoulder range of motion measurements have been associated with different injury risks and challenges in assessing rehabilitation progress. Variations in range of motion and torsion due to handedness in the asymptomatic professional population have yet to be investigated in the literature. Hypothesis: No significant differences in glenohumeral range of motion and humeral torsion would exist between asymptomatic right- and left-handed professional pitchers. Study Design: Cross-sectional study; Level of evidence, 3. Methods: 217 Major League Baseball pitchers from a single organization were evaluated over a 7-year period between 2013 and 2020. Range of motion was measured with a standard goniometer. Ultrasound scanning was used to determine neutral position of the shoulder, and the degree of humeral torsion was measured with a goniometer. Results: Right-handed pitchers demonstrated significantly greater values of glenohumeral external rotation (118.5° vs 112.7°; P < .001) in their throwing arms compared with their left-handed counterparts. Right-handed pitchers also showed greater values of glenohumeral internal rotation deficit (13.9° vs 4.8°; P < .001) and side-to-side differences in humeral retrotorsion (−23.1° vs −2.2°; P < .001). Left-handed pitchers demonstrated significantly greater flexion deficits in the throwing arm compared with their right-handed counterparts (7.5° vs 0.0°; P < .001). Conclusion: In the throwing arm, right-handed pitchers demonstrated significantly greater measures of external rotation, glenohumeral internal rotation deficit, and humeral retrotorsion compared with left-handed counterparts. Furthermore, right-handed pitchers demonstrated a significant side-to-side difference in retrotorsion, whereas left-handed pitchers did not. However, left-handed pitchers demonstrated a side-to-side shoulder flexion deficit that was not present in the cohort of right-handed pitchers. The correlation between humeral retrotorsion and increased external rotation indicates that osseous adaptations may play a role in range of motion differences associated with handedness. Additionally, these findings may explain observed differences in several throwing metrics between right- and left-handed pitchers. Knowledge of these differences can inform rehabilitation programs and shoulder maintenance regimens.